2021
DOI: 10.1590/0034-7167-2020-0431
|View full text |Cite
|
Sign up to set email alerts
|

Effects of clown activities on patients eligible for palliative care in primary health care

Abstract: Objective: Evaluate the effects of clown activities on quality of life, depression, stress, anxiety, aid, and social support in patients eligible for palliative care (PC) attended in Primary Health Care (PHC). Method: A quasi-experimental study, with pre-intervention and post-intervention evaluation, carried out with 16 patients eligible for early PC in PHC in a Midwestern city. Patients received 24 visits with home-based clown activities. Results: The interventions evidenced improved quality of life and soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…According to these results, HC accompanies children and families in PC, mediating and facilitating social relationships, being a bridge of magic and fantasy [ 38 ]. In addition to the evidence on its positive psychological and physiological effects on cancer patients [ 30 31 39 ], these results are in line with evidence showing that it has social effects, for example on the organizational climate of the hospital [ 40 41 ], and on the quality of life and social support of PC patients and families [ 32 ].…”
Section: Discussion Sectionsupporting
confidence: 80%
See 1 more Smart Citation
“…According to these results, HC accompanies children and families in PC, mediating and facilitating social relationships, being a bridge of magic and fantasy [ 38 ]. In addition to the evidence on its positive psychological and physiological effects on cancer patients [ 30 31 39 ], these results are in line with evidence showing that it has social effects, for example on the organizational climate of the hospital [ 40 41 ], and on the quality of life and social support of PC patients and families [ 32 ].…”
Section: Discussion Sectionsupporting
confidence: 80%
“…Moreover, previous evidence indicates that HCs have a positive effect in psychological [ 30 31 ] and physical [ 31 ] symptoms faced by PC oncological patients, improving their quality of life and social support [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Attrition has even been identified as a major problem in palliative care research [ 24 , 25 ]. We aimed to reduce attrition with a combination of patient-reported outcome questionnaires with physiological parameters [ 11 , 26 ]. Using the level of oxytocin in saliva as biomarker has been evaluated critically in the past [ 27 ] because of its strong concentration fluctuations and potentially not measurable amount in saliva.…”
Section: Discussionmentioning
confidence: 99%
“…In systematic reviews on the use of humor or laughter in palliative care patients, a number of studies reported that humor was useful for reducing the level of agitation, sadness, and depression; adapting to situations of depression and anxiety; managing fear; counteracting stress; transforming a more positive atmosphere; and expressing joy 3,6 . In contrast, Dos Santos et al 35 reported that clown activities inducing spontaneous laughter were not effective in reducing the anxiety and depression of palliative care patients who participated in their study. They explained the reason was that some patients’ conditions deteriorated while participating in the study.…”
Section: Discussionmentioning
confidence: 99%